2017
DOI: 10.1194/jlr.m076430
|View full text |Cite
|
Sign up to set email alerts
|

Microsomal triglyceride transfer protein in the ectoparasitic crustacean salmon louse (Lepeophtheirus salmonis)

Abstract: The salmon louse, Lepeophtheirus salmonis, is an endemic ectoparasite on salmonid fish that is challenging for the salmon farming industry and wild fish. Salmon lice produce high numbers of offspring, necessitating sequestration of large amounts of lipids into growing oocytes as a major energy source for larvae, most probably mediated by lipoproteins. The microsomal triglyceride transfer protein (MTP) is essential for the assembly of lipoproteins. Salmon lice have three L. salmonis MTP (LsMTP) transcript varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…In vertebrates, there are three MTP transcript variants that have been identified both in humans and mice, which turned out to encode two MTP isoforms in mice but only a single translation product in humans (Mohler et al, 2007 ; Suzuki and Swift, 2016 ; Suzuki et al, 2016 ). In agreement with our findings, sequence differences between transcript variants of MTP genes are also exclusively present in the 5′ end region in these species (Mohler et al, 2007 ; Suzuki and Swift, 2016 ; Suzuki et al, 2016 ; Khan et al, 2017 ). These findings indicated that transcription of the MTP gene might be conserved across animal phyla.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In vertebrates, there are three MTP transcript variants that have been identified both in humans and mice, which turned out to encode two MTP isoforms in mice but only a single translation product in humans (Mohler et al, 2007 ; Suzuki and Swift, 2016 ; Suzuki et al, 2016 ). In agreement with our findings, sequence differences between transcript variants of MTP genes are also exclusively present in the 5′ end region in these species (Mohler et al, 2007 ; Suzuki and Swift, 2016 ; Suzuki et al, 2016 ; Khan et al, 2017 ). These findings indicated that transcription of the MTP gene might be conserved across animal phyla.…”
Section: Discussionsupporting
confidence: 92%
“…According to transcriptome data, the three types of MTP transcript variants and/or MTP protein isoforms appear to be widely distributed in decapodan species ( Supplementary Figure 2 ). In fact, multiple MTP transcript variants and/or MTP protein isoforms are extensively observed in invertebrates and vertebrates (Mohler et al, 2007 ; Suzuki and Swift, 2016 ; Suzuki et al, 2016 ; Khan et al, 2017 ). For example, three MTP transcript variants were identified in the salmon louse Lepeophtheirus salmonis , and these were putatively translated into two MTP isoforms (Khan et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Female lice were fixed overnight while larvae, ovaries and unfertilized eggs were fixed for 2 hrs. Oil Red O stain was performed according to the previously described method [ 48 ] with some modifications in the length of time when adult lice were stained. After fixation, all samples were washed three times with ice-cold PBS and resuspended in 60% isopropanol for 10–30 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…RNA interference screens have aided the study of hostparasite interactions, host recognition (Komisarczuk et al, 2017;Núñez-Acuña et al, 2019), and physiology at various life stages of lice (Sandlund et al, 2016(Sandlund et al, , 2018Komisarczuk et al, 2018Komisarczuk et al, , 2020Braden et al, 2020;Guragain et al, 2020). RNAi has also facilitated in the functional studies of key genes involved in lice reproduction (Dalvin et al, 2009;Tröße et al, 2014;Eichner et al, 2015a;Khan et al, 2017;Borchel and Nilsen, 2018;Borchel et al, 2019;Heggland et al, 2019a,b). In addition, the method is used to identify the potential vaccine targets in C. rogercresseyi (Carpio et al, 2011;Maldonado-Aguayo and Gallardo-Escárate, 2014).…”
Section: Rna Interferencementioning
confidence: 99%